PENGEMBANGAN KEBUN WISATA PENDIDIKAN (KWP) UNNES MELALUI BIOEDUENTERPREUNERSHIP - Rahayuningsih, Margareta; Abdullah, Muh; Arifin, Samsul; N, Vitradesi (Badan Pengembang Konservasi UNNES, 2016)
Educational garden of Semarang State University has an area of about two hectares and developed since 2001. Initial management focuses on developing Jelajah Alam Sekitar (JAS) (exploring environment around). The potential of Unnes basically can be used as inventory for the campus environment, and therefore could be used as branding of Conservation University through creative and innovative products with the concept of empowerment. The purpose of this activity is the development and sustainability of the program in Educational Gardens of Unnes through Biodeduenterpreneurship. IbIKK Development of Educational Gardens of Unnes as Conservation University branding through the Bioeduenterpreunership has formed a business unit under the name